The Effectiveness of NHT Cooperative Learning Assisted with Picture Puzzle Towards Students’ Learning Activity and Outcomes in Plant Tissue’s Structure and Function Material - Prikadiastuti, Idaliani; Retnoningsih, Amin; Sumadi, Sumadi (FMIPA UNNES, 2017)
Limited number of microscope in a school become an obstacle to learning process, including to do anobservation to structure and function of tissue, especially from plants. This research discussed aboutplant tissue. Most students considered that this material was difficult due to limited number ofmicroscope and limited textbook information. Students became bored since the learning material wasdone only by listening and noting teachers’ explanation. The learning process suppose to make themactive, one of the alternative was by Numbered Head Together (NHT). The limited number ofmicroscope can be handled by the picture in picture puzzle. The purpose of this research was toanalyze the effectiveness of NHT with picture puzzle to the activity and learning outcome of studenstin plant tissue structure and function material. This research used pre-experimental with One ShotCase Study. The analysis of data included quantitative data to students’ activity, learning outcome,students’ opinion, and descriptive analysis to teacher’s opinion. The result of this research showed that91% of the students became active and very active. 82% of the students were also passed the score.Teacher and students gave positive reviews to the learning process. Based on the learning outcome, itwas concluded that the cooperative learning of NHT with picture puzzle was effective in increasingstudents’ learning activity and outcome in plant tissue function and structure material.